Robots For Economic Development - Massimiliano Calì; Giorgio Presidente (ZBW - Leibniz Information Centre for Economics, 2022)
Recent evidence suggests that automation technologies entail a trade-off between produc- tivity gains and employment losses for the economies that adopt them. This paper casts doubts on such trade-off in the context of a developing country. It shows significant productivity and employment gains from automation in Indonesian manufacturing during the years 2008-2015, a period of rapid increase in robot imports. Analysis based on manufacturing plant data provides evidence that the absence of this trade-off is due to diminishing productivity returns to robot adoption. As a result, the benefits from automation could be particularly large for countries at early stages of industrialisation, such as Indonesia. Suggestive evidence indicates these results could apply to developing countries more generally.
Keywords: 330; Robots; Automation; Development; Productivity; Employment